Laparoscopic sacral colpopexy for pelvic organ prolapse recurrence after transvaginal mesh surgery. (May 2020) - Campagna, Giuseppe; Panico, Giovanni; Vacca, Lorenzo; Caramazza, Daniela; Gallucci, Valeria; Rumolo, Valerio; Scambia, Giovanni; Ercoli, Alfredo
Abstract: Objective: Pelvic organ prolapse (POP) recurrence in transvaginal mesh surgery patients has become increasingly common, due to widespread mesh use before the FDA alert. The aim was to assess feasibility, effectiveness and safety of laparoscopic sacral colpopexy (LSCP) in recurrent POP after previous vaginal surgery with polypropylene mesh. Study design: Medical records of 20 patients with ≥ stage 2 POP recurrence, who underwent LSCP from January 2015 to July 2018, were retrospectively analyzed in a monocentric observational study. We analyzed operative time, intraoperative complications – defined as bowel, bladder, ureteral, or vascular injuries, post-operative complications - assessed with Clavien–Dindo's classification, and postoperative patient satisfaction - evaluated with the Patient Global Impression of Improvement questionnaire. Pre- and postoperative data were compared using t -test. Results: All women presented apical prolapse recurrence regardless of mesh type implanted and most of them involved the posterior compartment. No perioperative complications or cases of mesh extrusion, de novo urinary stress, urge incontinence, dyspareunia were recorded. At 12-month follow-up the POP-Q examinations demonstrated a statistically significant improvement of all parameters with a complete resolution of bulge, voiding and storage symptoms in all patients. Conclusion: LSCP suggests safety, feasible and efficacy in the treatment of recurrent POP after prior transvaginal polypropylene mesh surgery. We suggest to conduct a prospective research with larger sample size to gain further insights.